大采高液压支架用超大型底座柱窝模锻模具和成形方法 (2023)
本发明提供了一种大采高液压支架用超大型底座柱窝模锻模具，包括锻模，锻模包括上模和下模，锻模采用平直分模，上模上设置有球窝成型面，球窝成型面的球心相对锻件设计尺寸上移1.5-2.5mm，球窝成型面的窝口周边向下25-30mm范围内向外扩2-2.5mm；下模上设置有田字形分布的四个减重孔成型面，四个减重孔成型面的高度一致，减重孔成型面的侧立面拔模斜度为18-23°，减重孔成型面的底部圆角设置为R45-60，边缘位置圆角设置为R18-22，减重孔成型面的顶部转角处以SR460球面过渡；锻模的内腔侧面拔模斜度设置为4-6°。该模具满足了超大型锻件的加工要求，解决了超大型锻件的成形难题。 The invention provides an ultra-large base socket die forging die for a large mining height hydraulic support, which comprises a forging die, the forging die comprises an upper die and a lower die, the forging die adopts a straight split die, the upper die is provided with a ball socket forming surface, the ball center of the ball socket forming surface moves up by 1.5-2.5 mm relative to the design size of a forge piece, and the periphery of a socket opening of the ball socket forming surface expands outwards by 2-2.5 mm in a downward range of 25-30 mm; four lightening hole forming surfaces which are distributed in a shape like a Chinese character'tian 'are arranged on the lower die, the heights of the four lightening hol